2006
DOI: 10.1111/j.1365-2605.2006.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod‐induced apoptosis in the male genital tract epithelia of the golden hamster

Abstract: The aim of this study was to identify some details of the changes induced by a short-day light regime (8:16 light:dark) on the male genital tract and accessory sex glands of the golden hamster Mesocricetus auratus. We principally examined the presence of apoptotic cells in the epithelium from different regions of the epididymis, seminal vesicles, prostate and coagulating gland. We detected an increase in the percentage of apoptotic cells in situ using the TUNEL technique in animals that were maintained for 6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Our results show the expression levels of casp3 to significantly increase in DD samples compared to the other regimes suggesting that microbial communities may increase the occurrence of apoptosis. This finding is in agreement with Carballada et al, which identified the presence of apoptotic cells in the epithelium of the epididymis, seminal vesicles, prostate and coagulating gland of the golden hamster (Mesocricetus auratus) following a short-day light regimen (8:16 LD cycle) [89].…”
Section: Discussionsupporting
confidence: 92%
“…Our results show the expression levels of casp3 to significantly increase in DD samples compared to the other regimes suggesting that microbial communities may increase the occurrence of apoptosis. This finding is in agreement with Carballada et al, which identified the presence of apoptotic cells in the epithelium of the epididymis, seminal vesicles, prostate and coagulating gland of the golden hamster (Mesocricetus auratus) following a short-day light regimen (8:16 LD cycle) [89].…”
Section: Discussionsupporting
confidence: 92%
“…In the case of the aged epididymis the apoptotic changes observed were related to a fall in testosterone and a discrete decrease in androgen receptors (Jara et al, 2004). Furthermore, recent experiments demonstrated that a photoperiod-induced apoptosis occurs in the epididymis of the golden hamster (Carballada et al, 2007).…”
Section: Introductionmentioning
confidence: 93%